Antimicrobial resistance prevalence, rates of hospitalization with septicemia and rates of mortality with sepsis in adults in different US states - Goldstein, Edward (Int J Antimicrob Agents, 2019)
OBJECTIVES: Rates of hospitalization with sepsis/septicemia and associated mortality in the US have risen significantly during the last two decades. Antibiotic resistance may contribute to the rates of sepsis-related outcomes through lack of clearance of bacterial infections following antibiotic treatment during different stages of infection. However, there is limited information about the relation between prevalence of resistance to various antibiotics in different bacteria and rates of sepsis-related outcomes. METHODS: For different age groups of adults (18–49y,50–64y,65–74y,75–84y,85+y) and combinations of antibiotics/bacteria, we evaluated associations between state-specific prevalence (percentage) of resistant samples for a given combination of antibiotics/bacteria among catheter-associated urinary tract infections in the CDC Antibiotic Resistance Patient Safety Atlas data between 2011–2014 and rates of hospitalization with septicemia (ICD-9 codes 038.xx present on the discharge diagnosis) reported to the Healthcare Cost and Utilization Project (HCUP), as well as rates of mortality with sepsis (ICD-10 codes A40–41.xx present on death certificate). RESULTS: Among the different combinations of antibiotics/bacteria, prevalence of resistance to fluoroquinolones in E. coli had the strongest association with septicemia hospitalization rates for individuals aged over 50y, and with sepsis mortality rates for individuals aged 18–84y. A number of positive correlations between prevalence of resistance for different combinations of antibiotics/bacteria and septicemia hospitalization/sepsis mortality rates in adults were also found. CONCLUSIONS: Our findings, as well as our related work on the relation between antibiotic use and sepsis rates support the association between resistance to/use of certain antibiotics and rates of sepsis-related outcomes, suggesting the potential utility of antibiotic replacement.